Protective Effect of Membrane-Free Stem Cells against Lipopolysaccharide and Interferon-Gamma-Stimulated Inflammatory Responses in RAW 264.7 Macrophages - Mei Tong He (International Journal of Molecular Sciences, 2021)
Recently, adipose-derived stem cells (ADSCs) are considered to be ideal for application in cell therapy or tissue regeneration, mainly due to their wide availability and easy access. In this study, we examined the anti-inflammatory effects of membrane-free stem cell extract (MFSC-Ex) derived from ADSCs against lipopolysaccharide (LPS)/interferon-gamma (IFN-γ) on RAW 264.7 macrophage cells. Exposure of RAW macrophages to LPS and IFN-γ stimuli induced high levels of nitric oxide (NO), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE2) production. However, pretreatment with MFSC-Ex inhibited LPS/IFN-γ-induced these pro-inflammatory mediators. To clarify the molecular mechanisms underlying the anti-inflammatory property of MFSC-Ex, we analyzed nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs) protein expressions by Western blotting. Our study showed that treatment of MFSC-Ex significantly down-regulated inducible nitric oxide synthase (iNOS) and COX-2 protein expressions. Furthermore, phosphorylation of extracellular signal-regulated kinase (ERK) and p38 was also blocked by treatment with MFSC-Ex, indicating that inhibitory effect of MFSC-Ex on MAPK signaling cascade may attribute to inactivation of NF-κB. From these findings, we suggest that MFSC-Ex exert anti-inflammatory activities, which suppressed LPS/IFN-γ-induced production of NO, COX-2 and PGE2 by regulation of NF-κB and MAPK signaling pathway in RAW 264.7 macrophages. In conclusion, MFSC-Ex might provide a new therapeutic opportunity to treatment of inflammatory-related diseases.